Influence of annealing on X-ray diffraction of natural alexandrite - Scalvi, RMF; Ruggiero, L. D.; Li, M. S. (J C P D S-int Centre Diffraction Data, 2002)
In this work we present results of X-ray diffraction using powder method, on natural alexandrite samples from Minas Gerais State (Brazil), as a function of a sequence of annealing. From these measurements we determine lattice parameters before (a = 9.405 Angstrom, b = 5.471 Angstrom, c = 4.409 Angstrom) and after annealing, and its structure is confirmed as orthorhombic. Measurements done after an annealing of 15 minutes at 700 degreesC and for 5 hours at 1000 degreesC indicate the migration of atoms present in the sample through different phases, which were also identified by Microprobe Analysis (WDS). However we have verified that such migration does not modify the structure. X-ray diffraction measurements have been carried out in conjunction with optical absorption in the UV-Vis as a function of annealing. (C) 2002 International Centre for Diffraction Data.
Keywords: alexandrite; optical absorption; X-ray diffraction